Developmental experience of the geoinformation system for floodplain lands of the Don basin - D. A. Solodovnikov; S. S. Shinkarenko; N. M. Khavanskaya; N. A. Kukushkina (Юг России: экология, развитие)
Aim. The work describes the experience of developing a geographic information system for the floodplain lands of the Don basin. Playing a large role in the economy, river floodplains provide reproduction of hayfields and pastures, fish, waterfowl and birds which live near water, and in the arid zone they concentrate forest resources and wild animal populations. However, until the present there has been no single database that would allow us to analyse the most important characteristics of floodplain landscapes.Material and Methods. The implementation of the database elements was carried out using the following methods. The area of the river basin (tributary), the slope and exposure of the sides of the valley, the slope of the river bed and the length of the watercourse, the area of floodplains, agricultural land on floodplain lands, forest land, the tortuosity of the river and the development of the floodplain and the number, area and volume of small reservoirs were obtained by processing digital terrain models employing functions of the Spatial Analyst module and satellite images in automatic mode.Results. During this first stage of the study, the authors developed 14 important characteristics that form the basis of a modern database for the floodplains of the Don River Basin and determined algorithms and methods for calculating each indicator.Conclusion. The creation of a specialized geographic information system for the floodplain lands of the Don basin permits the solution of particular problems of data unification and the interaction of individual electronic atlas modules with each other and with the external resources of web‐mapping services and databases. The resulting atlas should find wide application in the areas of water and land management and nature conservation.